Analisis Penempatan dan Karakteristik Pekerjaan Terhadap Kepuasan Kerja - Panji Pramuditha (Tirtayasa Ekonomika, 2020)
This study aims to determine and analyze the presence or absence of the effect of work placement and job characteristics on job satisfaction both partially and simultaneously, considering that companies need to manage and develop human resources properly, because the key to company success is not only excellence in technology and availability of funds , but the human factor is also an important factor to achieve job satisfaction with employees of PT. Angkasa Pura II (Persero) Husein Sastranegara Airport which is expected to achieve organizational goals. This research uses descriptive verification method. Primary data in this study were obtained from the results of statements (questionnaires) distributed directly to 43 respondents of PT. Angkasa Pura II (Persero) Husein Sastranegara Airport, while secondary data were obtained from employee data of PT. Angkasa Pura II (Persero) Husein Sastranegara Airport. The analytical method used is multiple linear regression analysis using the SPSS v21.1 for Windows application and testing the hypothesis test of the t test and the statistical test of the f test. The results show that job work placement and characteristics have a significant effect on job satisfaction partially with a positive relationship direction of 0.754; job work placement and job characteristics have a significant effect on job satisfaction simultaneously showing positive correlations, and in the category of very strong relationships, meaning that the better the job work placement and characteristics, the better job satisfaction on employees.